Sources of Turkish EFL Learners’ Foreign Language Reading Anxiety - Cemre Isler; Ozgur Yildirim (JEELS (Journal of English Education and Linguistics Studies), 2017)
The purpose of this study was to investigate possible sources of reading anxiety experienced by Turkish EFL learners. The participants of the study were 50 first year university students studying at the English Language Teaching program of a public university in Turkey. The study employed the explanatory sequential mixed methods design. First, the quantitative data were collected through Foreign Language Reading Anxiety Scale (FLRAS), and then the qualitative data were collected through semi-structured interviews for the purpose of better understanding quantitative data findings. For analyzing the quantitative data, each participant's mean score from FLRAS was computed. As for the qualitative data, the transcribed interviews were analyzed using the constant comparison method, for which the researcher identified the recurring themes through coding, prioritizing and connecting the pieces of data. Results indicated that the participants of the study, in general, experience a moderate level of FL reading anxiety. The following three main categories of FL reading anxiety sources were identified with their ten sub-categories: (1) personal factors (inappropriate reading strategy use, lack of self-confidence, high expectations), (2) features of the reading text (topic familiarity, unknown vocabulary, complex reading structure, text length, figurative language), and (3) reading course (compulsory reading, exam).